An agile best practice framework for information technology project management / Jayasaegaran Sithambaram - Jayasaegaran , Sithambaram (2021)
The demand for success in IT projects is increasing, commanding careful attention to the factors impacting project success. Organisations are embracing the agile method due to its popularity and the benefits it yields. The agile manifesto provides a set of values and principles, but does not provide solutions for best practice in managing and delivering successful projects. Project issues and challenges are discussed in literature, with the absence of a best practice framework for the management of agile projects. This research aims to identify the factors from literature and the industry practitioners, to produce a validated best practice framework for the successful management of agile projects. A Systematic Literature Review initially compiled the factors impacting projects from the existing literature, followed by a Grounded Theory research which identified if the exact findings in literature are also impacting the industry practitioners. From 175 selected literature, 37 prominent factors affecting agile project success were identified. An initial list of 111 factors, along with proposed mitigation methods were then compiled from the industry practitioners. Comparing both findings, a list of 55 unique factors were produced using the Delphi technique, environmental scanning, and emerging issues analysis, segregating them into four categories: Organisation, People, Process and Technical. Various factors impacting agile projects were discussed in literature, with an absence of a holistic review to determine the critical factors which are impacting the success of projects in the industry. Project governance and the proper implementation of agile methods was the most addressed factor in literature, followed by people related factors. Literature suggests sound understanding of the agile principles with proper governance, by people with the right attitude, knowledge, skills and teamwork. The practitioners mainly discussed the process and people categories, with key issues on the misalignment of agile with the business objectives, the lack of understanding of agile principles, lack of teamwork and required skillset. The findings were used to develop a best practice framework evaluated by a panel of practitioners who found the framework comprehensive, relevant and applicable. A set of scenarios were created based on historical data, employing expert review to verify the validity, suitability and usefulness of the framework. The feedback received was verified against literature and used to fine-tune the framework and develop a tool, expected to assist in the successful management of agile projects. Keywords: